The First Record of a Marriage Cone, Conus sponsalis (Conidae: Gastropoda) from Korea - Joong-Ki Park (Animal Systematics, Evolution and Diversity, 2014)
The Conus Linnaeus, 1758 is a large genus of marine gastropod mollusks belonging to the family Conidae. The Conus species are mostly distributed in the tropical waters of the world, and they are especially abundant in the Indo-West Pacific region. To date, more than 600 species, most of which are predatory species, have been named worldwide in this genus and only six species have been recorded in the Korean waters. Conus sponsalis Hwass in Bruguiere, 1792 was collected from Jeju Island and identified as a new Korean record. In this study, we report a description of the shell morphology of the species.